PENERAPAN GENERAL SERVICE RULES DI MAKAN PLACE THE ZURI HOTEL PEKANBARU - Zulfia, Vioza Nurul; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Implementation is a planned activity with activities, actions, actions and the existence of a system mechanism to achieve activity goals. This study aims to find out how the application of general service rules at Makan Place Restaurant in welcoming guests, guiding and seating, checking comfort and seating, serving water, menu presentation, taking orders, suggestive selling, repeating orders, placing orders to system and kitchen, quality checking, food presentation , check satisfaction, offer dessert, clearing and crumbing, presenting the bill and thank the guest as well as any obstacles that occur in the application of general service rules in the Food & Beverage Service department of The Zuri Hotel Pekanbaru. Data collected using interview techniques, observation and documentation. Based on the research that was obtained from the results of the interviews that the application of the general service rule at the place restaurant The Zuri Hotel Pekanbaru can be said to be quite good because some have followed the procedure and some are still not in accordance with the procedure that has been determined. Keywords: Implementation, General service rule , Makan Place Restaurant, The Zuri Hotel Pekanbaru.